Indigenous Organizations and Rafael Correa’s Government - León, Jorge (2010)
This text analyzes the dynamic in relations between indigenous organizations and Rafael Correa’s government, first providing a very brief summary of these relations in previous administrations, especially those that followed the indigenous uprising of 1990. This event allowed indigenous people to claim a space on the political stage and to construct their own representation, which would, in turn, allow for progress in their demands for citadinidad. These demands have been presented primarily through the use of protests as a pressure mechanism. However, since the end of the 1990s, the indigenous organization has lost its points of reference and its ability to negotiate with the state. In this context, relations with the current administration, reveal a clear dispute between the two as regards demands for the recognition of difference and an increase in equality.